Faktor Risiko Kepatuhan Pengobatan pada Penderita Tb Paru BTA Positif - Rojali Rojali; Noviatuzzahrah Noviatuzzahrah (Politeknik Kesehatan Tanjung Karang, 2018)
This study was to determine the factors that affect the compliance of treatment of tuberculosis patients smear-positive pulmonary in Community Health Centers Cipondoh, Tangerang, Banten, the year 2015-2016. This research design was